Análise numérica de escoamento em vasos separadores verticais de compressores alternativos do tipo pistão - Fagner Patricio Lucas (2018)
The separator vessels are essential in reciprocating compressors units (API-618), for removing liquids from the gas flow and thus avoid their entry in the compressor cylinder. Considering that the experimental tests may be impractical, both in relation to the time as compared to the costs, the computational simulation has been shown as a useful tool for evaluation of separating vessels. Therefore, the objective of the present study was the numerical simulation of the air flow and water-air flow in six configurations of separator vessels, considering the influence of the wire mesh mist eliminator support ring (ENMF) and inlet devices. To this end, six geometric models were developed in a computer assisted design program and the mesh convergence test was performed. The mesh 2 with 1,115,883 nodes was the one that offered the shortest processing time among the meshes that converged, being the same one used in all simulations. On the other hand, the results obtained for the simulations with air flow indicated better results for the separating vessel with the support ring and with the inlet device proposed in the present work. This vessel showed a greater reduction of air inlet velocity (32 m.s-1 to 1.36 m.s-1), better flow uniformity (coefficient of variation equal to 0.18) and flow pattern less susceptible to breakup and re-entrainment of droplets in the air flow. The simulations with air flow and water droplets flow showed a lower influence of the support ring to the separator vessel with the proposed inlet device, due to the better uniformity of the flow inside the vessel. In addition, the flow pattern of the droplets, inside the vessel with the proposed input device, created conditions more favorable to the separation of the droplets in the ENMF.